Innovations in Addressing Menstrual Poverty in Africa: The Menstrual Cup Intervention for Girls in Rural Ghana - Nyanteng, Kofi Kyeremateng; Denning, Christine Garde (British Journal of Healthcare and Medical Research, 2024)
Background: Period poverty does not receive the needed attention and poses a major threat to the development of women and girls especially in developing countries. The well-known problem of accessibility and affordability of menstrual products likely suggests that women and girls go through a lot in going about their normal duties whenever they menstruate. They either half-heartedly attend to daily routines and other relevant activities or forgo them entirely because of the physical discomfort, psychological distress and feelings of low self-esteem (Mason et al., 2019) due to stigmatization and difficult access to menstrual absorbents. In 2021, a study funded by Plan International in the Wa East district of Ghana found 83% of rural girls who had no access to menstrual products and transacted sex for pads due to the problem of accessibility and affordability. CouldYou?, a US based non-profit responded to this developmental challenge as the organizations role in addressing Sustainable Development Goals (SDGs) 1,3,4, 5, and 17. CouldYou? collaborated with Ghana Girl Guides Association , and Plan International supported non-profits - Necessary Aid Alliance and Upper West Youth Parliament. The menstrual cup intervention reached 2,000 girls in the Wa East District. With this backdrop, this current study offers more insights into how the menstrual cup has become an innovative solution to fighting period poverty in rural Ghana. Methods: The menstrual cup intervention in Ghana covered the period November 2022 to July 2023 on a sample size of 385 girls who received the CouldYou? menstrual cup. Participants were selected from four communities in the Wa East District including Funsi, Goripie, Jumo, and Piisi. Age ranged between twelve (12) and twenty-eight (28) years. Community-based participatory research (CBPR) tools were used to record views and elicit rich responses from the girls. Quantitative surveys were conducted using KoboCollect. The qualitative data, on the other hand, was collected through semi-structured interviews. Findings: The introduction of the menstrual cup has led to some significant changes in rural girls managing their period. The study has found the menstrual cup as a dominant product with an acceptability rate of 97% in Wa East, significantly (p=0.00) improving accessibility to hygienic products and reducing the in-take of unhygienic products. A major finding is the complementary and substitutive role the menstrual cup is playing in addressing menstrual poverty. As a substitute, the cup has replaced the usage of old cloths/rags significantly. Beyond substituting the unhygienic products, some beneficiaries are adopting the cup as the next best alternative to the menstrual pads. As a complement, girls use the menstrual cup in addition to menstrual pads citing the economic advantages of the cup and the difficulty in affording menstrual pads. Conclusion: The study concludes that the menstrual cup has influenced accessibility to hygienic products and reduced the usage of unhygienic menstrual products. Whiles access to affordable sanitary pad is difficult in the rural communities of Wa East, the introduction of the menstrual cup offers an innovative and sustainable approach to fighting period poverty in Ghana.